SUSTAINABLE BUSINESS PRACTICES AND CONSUMER PREFERENCE: A STUDY OF ECO-FRIENDLY TOURISM IN BALI - Gede Andika; Muhammad Williams Rahaditama; Kornelius Sembiring; I Gede Travis Kus Mercury; Ida Bagus Adimerta Kawi (Journal of Economic, Bussines and Accounting (COSTING), 2026)
This study examines the influence of environmental sustainability practices, social sustainability practices, and sustainability certification and transparency on customer satisfaction and loyalty in Bali's eco-friendly tourism sector, while controlling for demographic and behavioral factors. A cross-sectional survey was conducted with 128 domestic and international tourists who had experienced eco-friendly accommodations in Bali. Multiple linear regression analysis was employed to test the relationships between sustainability practices and customer outcomes, controlling for gender, age, income level, and length of stay. Reliability and validity were established through Cronbach's alpha coefficients (α = 0.79-0.88) and exploratory factor analysis (KMO = 0.81). The integrated model explained 59% of variance in customer satisfaction and loyalty (Adjusted R² = 0.59, F(6,121) = 21.47, p < .001). Environmental sustainability practices emerged as the strongest predictor (β = 0.35, p < .001), followed by social sustainability practices (β = 0.29, p < .001) and sustainability certification and transparency (β = 0.21, p = .004). Income level (β = 0.17, p = .020) and length of stay (β = 0.14, p = .047) significantly influenced outcomes, while demographic variables (gender, age) showed no significant effects. Tourism businesses in Bali should prioritize visible environmental actions, integrate community-based initiatives, and pursue credible sustainability certifications to enhance competitive advantage through customer satisfaction and loyalty. Policymakers should develop comprehensive sustainability standards that encompass environmental, social, and transparency dimensions. This study advances sustainable tourism scholarship by simultaneously examining multiple sustainability dimensions with rigorous demographic and behavioral controls in a high-pressure tourism destination context.